Development of a photocuring system for cationic epoxy formulations using side emitting optical fibres - Al-Obaidani, Ammar (2009)
Photocuring of polymers and polymer composites, from epoxy resin based formulations, has been of growing interest over the past two decades. The photocuring occurs when an epoxy formulation is exposed to electromagnetic radiation, usually ultraviolet (UV) radiation. This process has been explored widely and it can be described as an open mould process by which the epoxy formulation is exposed directly to the radiation. However, for a closed mould process, thermal curing, rather than radiation curing, typically is employed. The potential of using photocuring for a closed mould process has not yet been investigated in detail. The challenge in photocuring of polymers and polymer composites in a closed mould is directing the radiation into the mould to activate the photocuring process, which is not possible using the conventional methods. Hence, for this reason the present work is focused on the development of a closed mould photocuring system using side emitting optical fibres.